Development of Multimedia-Based PAI Learning for Access to the Digital World in Enhancing the Understanding of Religious Concepts - Azzahra, Rahma Tiara; Sholiha, Alfiatus; Sihabudin, Sihabudin (International Journal of Instructional Technology, 2022)
Islamic Religious Education (PAI) has a very important role in shaping students' understanding and awareness of religious concepts. However, in the era of technological advances and increasingly widespread internet penetration, teaching PAI is becoming increasingly complex. Therefore, the development of multimedia-based PAI learning and utilizing access to the digital world is relevant in increasing students' understanding of religious concepts. Several previous studies have shown the potential for using multimedia in PAI learning to increase student understanding, learning motivation, and active involvement in the learning process. However, there are still some problems that need to be addressed, such as the teacher's lack of understanding of the potential of multimedia, limited resources, and the selection of relevant material in the context of PAI learning. The purpose of this study was to explore and develop a multimedia-based Islamic Religious Education learning approach and evaluate its effectiveness in increasing students' understanding of religious concepts. The research methods used include interviews, observation, questionnaires, surveys, document analysis, and other data collection techniques. The results of the study show that the use of multimedia in PAI learning can significantly increase students' understanding. However, the teacher's skills in integrating multimedia and the availability of adequate resources greatly affect the implementation of learning. In addition, the selection of relevant material is also an important factor in increasing the effectiveness of multimedia-based PAI learning. To increase the effectiveness of multimedia-based PAI learning, efforts are needed in terms of teacher training, adequate resources and infrastructure support, as well as the selection of material that is relevant to the learning context. By paying attention to these factors, the use of multimedia in PAI learning can be an effective and sustainable alternative to increase students' understanding of religious concepts. This research is expected to contribute to the development and implementation of Islamic Islamic education learning that is innovative and in accordance with the times